Roles of single interpolation and statistical distributions on application in air quality data sets: An overview - Norazian, Mohamed Noor; Mohd Lutfi, Zainudin (Universiti Kebangsaan Malaysia (UKM), 2011)
Regional Engineering Postgraduate Conference 2009 (EPC 2009) organized by Faculty of Engineering & Built Environment, Universiti Kebangsaan Malaysia, from 20th - 21st October 2009 at Palm Garden Hotel, Putrajaya, Malaysia.